Development and Characterization of Poly(1-vinylpyrrolidone-co-vinyl acetate) Copolymer Based Polymer Electrolytes - Nurul Nadiah Sa’adun; Ramesh Subramaniam; Ramesh Kasi (The Scientific World Journal)
Gel polymer electrolytes (GPEs) are developed using poly(1-vinylpyrrolidone-co-vinyl acetate) [P(VP-co-VAc)] as the host polymer, lithium bis(trifluoromethane) sulfonimide [LiTFSI] as the lithium salt and ionic liquid, and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide [EMImTFSI] by using solution casting technique. The effect of ionic liquid on ionic conductivity is studied and the optimum ionic conductivity at room temperature is found to be 2.14 × 10−6 S cm−1 for sample containing 25 wt% of EMImTFSI. The temperature dependence of ionic conductivity from 303 K to 353 K exhibits Arrhenius plot behaviour. The thermal stability of the polymer electrolyte system is studied by using thermogravimetric analysis (TGA) while the structural and morphological properties of the polymer electrolyte is studied by using Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction analysis (XRD), respectively.